Desain Dan Simulasi Maximum Power Point Tracking (Mppt) Perturb And Observe (P&O) Dengan Kendali Arduino Untuk Pembangkit Listrik Tenaga Angin Kecepatan Rendah - Melaluca Leuca Dendron Kadarnis; Amir Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Wind power plants are power plants that compose wind energy to produce electricity. With a Permanent Magnet synchronous generator or better known as PMSG (Permanent Magnet Synchronous Generator) is a generator by using a permanent magnet in the stator so that it can excite itself. MPPT P & O (Maximum Perturb and Observe Power Point Tracking) is implemented using a buck-boost converter to find the maximum power value used to charge 28V batteries. The design and analysis of buck boost converter modeling has been made and simulated using Proteus pro 8.6 by using Arduino as a duty-cycle controller. The results of the MPPT P & O algorithm that is inserted into Arduino are able to vary the width of the duty cycles to control battery loading while maintaining a safe limit on battery charging voltage.Key word: PMSG, MPPT P&O, Buck-Boost Converter, Arduino, Proteus Profesional 8.6